On Discovering Doctrine: “Justice” in Contract Agreement - Peter A. Alces (Washington University Law Quarterly, 2005)
I pursue here what might be termed “doctrinal jurisprudence”: Study of the way facts (including rules) become legal doctrine, specifically here how idiosyncratic perceptions concerning “justice” facts support the development of contract agreement doctrine. This Article investigates the relationship between the way we encounter data (including laws, and specifically a contract law) and what we may conclude about the Law, as doctrine, that emerges from that encounter.
Keywords: Contract theory; Justice; Contracts; Cognitive science; United States